Variation in Coarse Particulate Matter (PM10) and Its Characterization at Multiple Locations in the Semiarid Region - Zeb, Bahadar; Alam, Khan; Ditta, Allah; Ullah, Sami; Ali, Hayssam M.; Ibrahim, Muhammad; Salem, Mohamed Z.M. (Frontiers in Environmental Science, 2022)
Introduction: The elemental composition and morphological study of particulate matter are very important to understand the nature of particles influencing the environment, climate, soil, and health. Methods: The PM10 samples were collected during the winter season (2018) in Nowshera city, KPK (Pakistan) over three locations i.e. urban, industrial and suburban. Scanning Electron Microscopy (SEM) and Electron Dispersive X-ray (EDX) spectroscopy were used to examine the PM samples for morphological examination and elemental composition. Results: The average mass concentrations of particulate matter (PM10) at the urban, industrial and suburban locations were 238.5, 505.1, and 255.0 µg m-3, respectively. The average PM10 mass concentration was higher above the WHO and National Ambient Air Quality Standards (NAAQS). The results of EDX showed that samples contained variable amounts of thirteen elements i.e. oxygen, carbon, silicon, magnesium, sodium, calcium, iron, aluminum, potassium, sulfur, titanium, gold, and chlorine. The probable sources of PM were biogenic like plant debris, pollens, and diatoms, geogenic like road dust, resuspended soil dust, and anthropogenic i.e. carbonaceous particles, fly ash as confirmed by SEM–EDX. The carbonaceous species i.e. OC and EC had average values of 55.8±13.1 and 4.6±0.6, 5.2±3.2 and 36.4±10.4, 40.0±2.6 and, 6.3±0.2 over industrial, urban, and suburban locations, respectively. Similarly, OC/EC had average values of 12.0±1.2, 8.0 ±3.0, and 6.3±0.2 over industrial, urban, and suburban locations, respectively. Highly significant correlations among water-soluble ion (K+), OC, and EC were found in each location. Conclusions: The examined PM10 mass concentration in Nowshera city was above the thresholds of National Ambient Air Quality Standards (NAAQS) set by the United States Environmental Protection Agency (EPA). In addition, the concentration of pollutants was the highest at the industrial site compared to the other sites. The HYSPLIT model showed that the air mass originated from local sources like cement industries, brick Kiln industries, and others.